Product analysis, electrical and dielectric properties depending on thermal influence of poly(N-isopropyl acrylamide)/graphite-filled composite - Biryan, Fatih; Abubakar, Abdullahi Musa; Demirelli, Kadir (Elsevier Science Bv, 2018)
The ac dielectric and electrical behaviors of the pure poly(N-isopropylacrylamide) (PNIPAM) and PNIPAM/8% by wt graphite-filled composite at room temperature and that of partially degraded polymer were investigated. TGA measurements showed that thermal degradation of the pure PNIPAM and PNIPAM/8% by wt graphite-filled composite polymers were a single-stage process under nitrogen atmosphere. Phenomenon of depolymerization from thermal degradation of PNIPAM and PNIPAM/8% by wt graphite-filled composite was revealed as a significant difference in comparison to polyacrylamide and other analogous. In degradation studies, while the N-isopropylacrylamide was detected as 25% by mole among products of degradation of PNIPAM/8% graphite filled composite, this event was 9% by mole for that of pure PNIPMA. The major evolved products were found to be molecules such as N-isopropylacrylamide, cyclic-imides, diisopropylamine, dimer and trimer. Degradation mechanism of the polymer was briefly suggested and evaluated the relationship between structures of the pure PNIPAM and PNIPAM/8% graphite-filled composite polymers.
Keywords: Thermal degradation; Dielectric properties; Poly(NIPAM)